Prevalence of injuries among medicaid enrolled infants prior to child abuse and neglect - Shanahan, Meghan E. (Child maltreatment, 2022)
Prior research has identified common injuries among children who experience child maltreatment; however, most of this work has focused on inpatient settings and has excluded many cases of neglect. This study examines the prevalence of injuries that occur prior to a diagnosis of child maltreatment, as well as the proportion of children with well-child visits prior to the injury and child maltreatment diagnosis. Based on a secondary analysis of Medicaid data from four states, we found that among infants with 12 months of continuous enrollment (N = 4817), 30.6% of those diagnosed with maltreatment were previously diagnosed with an injury. Among infants diagnosed with child maltreatment, 88.4% had at least one well-child visit prior to the maltreatment diagnosis. Among children with a maltreatment diagnosis and a prior injury, 84% had at least one well-child visit preceding the injury. These results indicate that most children had at least one well-child visit prior to being diagnosed with child maltreatment or an injury, indicating opportunities for prevention.